2017
DOI: 10.1016/j.neuroimage.2016.09.034
|View full text |Cite
|
Sign up to set email alerts
|

The neurogenesis of P1 and N1: A concurrent EEG/LFP study

Abstract: It is generally recognised that event related potentials (ERPs) of electroencephalogram (EEG) primarily reflect summed post-synaptic activity of the local pyramidal neural population(s). However, it is still not understood how the positive and negative deflections (e.g. P1, N1 etc) observed in ERP recordings are related to the underlying excitatory and inhibitory post-synaptic activity. We investigated the neurogenesis of P1 and N1 in ERPs by pharmacologically manipulating inhibitory post-synaptic activity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 117 publications
(149 reference statements)
4
43
2
Order By: Relevance
“…This contrasts with previous reports that these bi-phasic deflections reflect sequences of excitatory (P1) followed by inhibitory (N1) post-synaptic inputs (Tan et al, 2004 ; Oswald et al, 2006 ). However, a similar finding was reported in a recent study of rat somatosensory cortex where reduced inhibitory post-synaptic activity affected only the late phase of the N1 by increasing its peak and duration (Bruyns-Haylett et al, 2017 ). Based on the time course and morphology of the simulated LFP components, we speculate that the initial positivity (P1) reflected bottom-up activity of the basal dendrites of pyramidal neurons in layers II/III as shown in Figure 4 .…”
Section: Discussionsupporting
confidence: 86%
“…This contrasts with previous reports that these bi-phasic deflections reflect sequences of excitatory (P1) followed by inhibitory (N1) post-synaptic inputs (Tan et al, 2004 ; Oswald et al, 2006 ). However, a similar finding was reported in a recent study of rat somatosensory cortex where reduced inhibitory post-synaptic activity affected only the late phase of the N1 by increasing its peak and duration (Bruyns-Haylett et al, 2017 ). Based on the time course and morphology of the simulated LFP components, we speculate that the initial positivity (P1) reflected bottom-up activity of the basal dendrites of pyramidal neurons in layers II/III as shown in Figure 4 .…”
Section: Discussionsupporting
confidence: 86%
“…Finally, comparison of the temporal dynamics of the ERP and that of the evoked LFP across cortical layers suggest that somatosensory evoked potential reflects better the LFP in the supragranular layer of the cortex than that in the granular and infragranular layers. This is in agreement with our earlier work 6 , demonstrating that the initial segment (P1) of the ERP is related to the return current arising from the inflow of the excitatory synaptic current occurring in the granular layer, while the subsequent decrease (N1) in ERP may be related to the delayed arrival of thalamic afferent to cortical layers II/III and/or feedforward signals from deeper cortical layers. In conclusion, concurrent recordings of EEG/LFP can enhance understanding of the neural genesis of EEG, and facilitate the mathematical modeling of EEG in terms of neural signals across cortical layers.…”
Section: Discussionsupporting
confidence: 93%
“…It is generally accepted that LFPs recorded via microelectrodes primarily reflect the weighted sum of synchronized excitatory and inhibitory synaptic activities of local pyramidal neural populations 1 2 3 4 . Our recent research demonstrated that the profile of the LFP signal could be separated into components of excitation and inhibition 5 6 . However, as LFP is normally measured via an invasive procedure, it is not suited for most studies of the human brain.…”
Section: Introductionmentioning
confidence: 99%
“…The neural response to low-level visual stimuli, measured through the visual evoked potential (VEP), is the net result of excitatory and inhibitory mechanisms governing many low-level visual features. The direct effect of inhibitory processes on the VEP has been demonstrated by applying a GABA A antagonist to visual and somatosensory cortices of animal models (Bruyns-Haylett et al 2017;Daniels and Pettigrew 1975;V Zemon et al 1980). These studies show that specific positive and negative aspects of the VEP time series are increased and decreased in magnitude following topical application of a GABA antagonist to the visual cortex of cats (V Zemon et al 1980;Vance Zemon, Kaplan, et al 1986).…”
Section: Ssvep To Assay Lateral Interactionsmentioning
confidence: 94%